Discursive positioning of beginning teachers' professional learning during induction: a critical literature review from 2004 to 2014. Issue 5 (20th October 2017) - Simmie, Geraldine Mooney; de Paor, Cathal; Liston, Jennifer; O'Shea, John
ABSTRACT: This study reports on findings from a critical literature review, from 2004 to 2014, in relation to the positioning of beginning teachers' professional learning during induction. The study uses theoretical frameworks drawn from competing discourses: an instrumental standpoint based on performativity and a dialectical standpoint based on a transformative view of good teaching as an advanced specialised practice. A critical analysis was conducted, using a systematic literature review that yielded 14 peer-reviewed papers, to discursively position teachers' professional learning and pinpoint questions for future study. Findings showed that while studies reported positive outcomes they were often atheoretical and framed within narrow chains of logic that neglected important strands, such as, teacher "knowledge-of-practice". The study raises important questions not only about the positioning of beginning teachers' professional learning but about meaningful professional learning for all teachers across the continuum of teacher education.